Integrated Project Teams: the way forward for UK defence procurement - Moore, David M.; Antill, Peter D. (Cranfield University, 2001)
This paper looks at a particular aspect of the Smart Procurement Initiative, which was announced in the Strategic Defence Review, that of Integrated Project Teams. These teams aim to bring together all the relevent stakeholders from the Ministry of Defence, armed forces and industry. Much has been written on the perceived benefits these teams will bring to the procurement process in their management of a project from 'cradle to grave'. This paper examines the potential pitfalls that lay ahead and the factors the Ministry of Defence will have to take into account in order for them to succeed.